Histological Examination and Gene Expression Profiles of CpLAX2, CpLAX3 and CpPIN4 during Somatic Embryogenesis in Carica papaya - Baker, Al-Shara; Jamaludin, Mohamad; Rosna, Mat Taha; Wesam, Al Khateeb; Hashimah, Elias; Asif, Khan; Mohammad, Jawarneh (Friends Science Publishers, Faisalabad, Pakistan, 2025)
Histological and molecular examinations were performed on somatic embryos derived from 'Eksotika' papaya; including immature zygotic embryos, throughout somatic embryogenesis process. To overcome the challenges in regenerating somatic embryos from immature zygotic embryos of "Eksotika", this study specifically focused on understanding callus development at the bases of somatic embryos. Somatic embryogenesis systems serve as valuable models for studying the molecular, regulatory, and morphogenetic processes involved in plant embryogenesis. Light microscopy and quantitative real-time PCR were employed to examine the histological and molecular changes during the developmental stages of somatic embryogenesis and callus formation at the bases of somatic embryos. The accumulation of secondary somatic embryos on the root surface, particularly in the root cap zone, represents the most significant obstacle to successful somatic embryo formation. Different developmental stages, starting from pro-embryos to cotyledonary phases, were found to be quite similar to the ontogeny of zygotic embryos. All selected genes: (Carica papaya PIN-FORMED (auxin efflux carriers) CpPIN4, Carica papaya AUXIN RESISTENT 1/LIKE AUX1 (AUX/LAX) (auxin influx carriers) (CpLAX3 and CpLAX2) were clearly expressed in somatic embryos formed during the induction phases of somatic embryogenesis. CpLAX3 exhibited the highest expression levels among the selected tested genes, while CpPIN4 showed the lowest. The formation and development of somatic embryos involved the expression of all selected genes.